2019
DOI: 10.1139/cjss-2018-0146
|View full text |Cite
|
Sign up to set email alerts
|

Soil health indicators after 21 yr of no-tillage in south coastal British Columbia

Abstract: The lower Fraser Valley is one of the most intensively cropped regions in Canada. Yet, how soil health indicators respond to long-term intensive agricultural management is poorly documented in this region. Thus, we evaluated a suite of soil health indicators in response to 21 growing seasons of continuous silage corn (Zea mays L.) under conventional tillage or no-tillage (0–20 cm soil layer). Wet aggregate stability, available water capacity, active carbon (permanganate oxidizable, POXC), and extractable potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In China, managing a silty clay loam Mollisol without tillage had more macroaggregates and greater MWD of WSA than this soil managed with tillage (Yan et al, 2020). Thomas et al (2019) reported that WSA measured with a rainfall simulator nearly doubled under NT compared with conventional tillage (moldboard plow) on silt loam soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, managing a silty clay loam Mollisol without tillage had more macroaggregates and greater MWD of WSA than this soil managed with tillage (Yan et al, 2020). Thomas et al (2019) reported that WSA measured with a rainfall simulator nearly doubled under NT compared with conventional tillage (moldboard plow) on silt loam soil.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al. (2019) reported that WSA measured with a rainfall simulator nearly doubled under NT compared with conventional tillage (moldboard plow) on silt loam soil.…”
Section: Discussionmentioning
confidence: 99%
“…However, soil factors and topography as indicators were selected only in the traditional farmland quality assessment [47]. The ecological conditions of farmland have not been adequately considered in current research [59]. Therefore, it is particularly important to establish an index system that considers both socioeconomic factors and the ecological environment.…”
Section: Superiority Testmentioning
confidence: 99%
“…Soil tillage is a vital cultural practice to control soil water, soil nutrients, and soil temperature (Yang et al 2018). In many dry regions, conversion from conventional tillage to conservation tillage is a promising strategy to improve soil structure (Martínez et al 2013;Pareja-Sánchez et al 2017), preserve soil water (Jin et al 2007(Jin et al , 2008, and enhance the accumulation of SOC (Sun et al 2018a;Thomas et al 2019;Wang and Zou 2020a). For instance, it has been shown that long-term no tillage with mulch (NT) improved the capacity of the soil to store and conserve water, to increase the content of dissolved organic carbon and available nutrients through retaining more crop residues (Singh et al 2019); subsoiling with mulch (SS) also proved to be an effective strategy to increase soil water content by stimulating water infiltration, and increasing soil carbon and nitrogen concentrations (Wang et al 2020b); reduced tillage (RT) also served as a conservation tillage practice and could increase the content of SOC by reducing the number of tillage operations.…”
Section: Introductionmentioning
confidence: 99%